Challenging passivity in venous leg ulcer care – the ABC model of management. Issue 6 (5th May 2016) - Harding, Keith
Abstract: The under‐utilisation of compression for venous leg ulcer (VLU) management translates into lost opportunities to heal wounds, improve patients' quality of life and maximise health care system efficiency. Although compression therapy is considered gold standard according to clinical guidelines, lack of clinician knowledge, unclear referral pathways, local unavailability of compression and patient unwillingness to receive compression, amongst other reasons, mean many candidates for compression do not receive appropriate treatment. This article presents a solution in the form of the 'ABC model of VLU management, a simplified approach that challenges passivity in the current approach to VLU treatment and supports wider adoption of appropriate compression therapy systems.